MPPT using Firefly Algorithm for Cuk Converter in Photovoltaic - Denda Dewatama; Siswoko Siswoko; Hari Kurnia Safitri; Oktriza Melfazen (ELKHA : Jurnal Teknik Elektro, 2022)
High intensity of sunlight in Indonesia (up to 10 hours per day) is a great opportunity to be utilized as renewable energy by absorbing solar energy using solar panels. The absorbed solar energy is channeled into a DC/DC converter circuit with a Cuk converter topology so that it can be used with small current ripples. The Maximum Power Point Tracker (MPPT) method is needed to get optimum power from solar panels. To optimize the MPPT value, its performance is supported by using the Firefly Algorithm (FFA). This study focused on observing changes in FFA parameters, i.e., firefly populations and random parameters to generate optimal power on Cuk converter topology with MPPT method. FFA embedded in microcontrollers has successfully optimized MPPT performance with the best response obtained in the firefly population = 25, absorption coefficient (γ) = 0.5, random value (α) = 0.6, iteration = 10, with an optimal power of 25.7 Watts.